Transformation of Record Keeping: Development of E-Archive Applications Towards Modern Information Governance - Santosa, Firman (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The transformation of record-keeping through technology-driven approaches has become an urgent necessity in addressing the demands of modern information governance. This study explores and analyzes the challenges encountered and solutions adopted during the implementation of the E-Archive application in the Modern Market of Rokan Hulu Regency. The deployment of this application, which is web-based and utilizes a MySQL database, involves requirements analysis, design, development, and implementation phases. The research findings highlight that this transformation has positively impacted record-keeping, enhancing efficiency, speed of access, and data accuracy. Nevertheless, the study also identifies several issues, including challenges in data collection and migration, as well as user adaptation to the new system. The web-based technology solutions and MySQL database, while offering solutions for some aspects, also bring certain challenges. The results of this research provide valuable insights into the potential and constraints of implementing the E-Archive application in the context of the modern market and similar sectors. Moreover, it underscores the importance of understanding and addressing issues throughout the information governance transformation process.